THE COMBINATION OF CHITOSAN-NUTMEG EXTRACT FOR THE NATURAL ANTIBACTERIA AND PRESERVATIVE AGENTS OF RED SNAPPER (Lutjanus sp.) FILLET - Nastiti Siswi Indrasti, Suprihatin dan Wahyu Kamal Setiawan TIP (Jurnal Teknologi Industri Pertanian, 2012)
ABSTRACT   Chitosan is produced by deacetylation of chitins which are found in the outer shell of crustacea such as shrimps and crabs. The ability of chitosan as an agent of antibacte ria depends on the degree of deacetylation. This experimental work aimed to study the possibility of chitosan as natural antibacteria of red snapper fillet. The experiments were carried out   in three steps. The first step was the production of chitosan from shrimp shells. The produced chitosan was analyzed by FTIR (Fourier Transform Infra Red) and proximate analysis. The second step was investigation of antibacterial  activity of chitosan and its combination with nutmeg extract. The concentrations of chitosan were  varied 1%; 1.5%; and 2% (w/v) while nutmeg extract were  0%, 5% and 10%. The final step was application of the best combination for red snapper fillet preservation by the dipping method. The chitosan produced in this research meet the commercial standard: particle size, colour of extract, water content (7.89%), ash content (0.79%), and degree of deacetylation (73.86%). Combination of chitosan 1.5% and nutmeg extract 10% showed synergic inhibition againts Escherichia coli with an inhibition diameter of 34.60 ± 0.57 mm. Combination of 1.5% chitosan and 10% nutmeg extract inhibited  the growth rate of bacteria on red snapper fillet (Sig